The Shift in Family Breadwinning Roles from Husbands to Wives in Islamic Family Law - Rahmadhani Simatupang; Heri Firmansyah; Nurcahaya Nurcahaya (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The shift in family breadwinning roles from husbands to wives has become increasingly common among Muslim families in Indonesia due to changing socio-economic conditions. This study aims to analyze the forms and determinants of breadwinner role shifts among Muslim families in Tanjung Balai City and examine their implications from the perspectives of Islamic Family Law and Indonesian Positive Law. This study employed empirical legal research using a qualitative case study approach. Data were collected through in-depth interviews, observations, and documentation involving 21 informants, including working wives, husbands, religious leaders, community leaders, local government officials, and family law experts. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while credibility was ensured through source triangulation, technique triangulation, and member checking. The findings reveal that the shift in breadwinner roles is primarily driven by unstable household income, increasing living costs, children's educational expenses, and expanding economic opportunities for women. Although many wives become the primary income earners, the Muslim community continues to recognize the husband as the person primarily responsible for family maintenance. Wives' economic contributions are interpreted as a manifestation of ta'āwun (mutual assistance), 'adl (justice), musyāwarah (consultation), and maṣlaḥah (public welfare), rather than a transfer of the husband's legal obligation. However, the increased economic participation of wives has not been accompanied by an equal redistribution of domestic responsibilities, resulting in a persistent double burden. The novelty of this study lies in the development of a conceptual framework integrating socio-economic adaptation with the perspectives of Islamic Family Law and Indonesian Positive Law. The findings contribute to the contextual development of Islamic Family Law and provide practical recommendations for strengthening family resilience through equitable cooperation, effective communication, and balanced family responsibilities.